An effective strategy for species identification of avian meats using the mitochondrial 12S rRNA gene fragment. (24th January 2014) - Wang, Lan-Ping; Geng, Rong-Qing; Liu, Zhong-Quan
Abstract: An effective DNA-based molecular method had been used to identify avian species from meats. The method combined the use of a pair of universal primers, which amplified about 440-bp fragment of the mitochondrial 12S rRNA gene. A total of 99 meat samples were tested and 17 haplotypes were identified by DNA sequencing, which representing 14 avian species. One avian species was listed as the national first-grade protected animal in China and the IUCN endangered species. Two avian species were under the national second-grade state protection. The proposed method represents a straightforward and robust method for the accurate identification of avian species that could be used by law enforcement agencies as a tool for the control of illegal trade of meat from protected species.